Response of Lettuce (Lactuca sativa L.) To Aquaculture Wastewater Treatment - Mumpuni, Fia Sri; Yulianti, Nani; Maryani, Yeni (Journal of Tropical Crop Science, 2023)
The fish feed waste and litters are organic matter that can be a source of nutrients for plants. This study is aimed to determine the growth and production of lettuce (Lactuca sativa L.) treated with wastewater from hard-lipped barb culture of several population densities. The research was carried out from April through June of 2020 at the greenhouse of the Agrotechnology Study Program, Faculty of Agriculture, Djuanda University, Bogor, Indonesia. The controlled study used a randomized block design with one factor, wastewater from fish population density of 10, 20 and 30 per 21 L of water, and AB Mix as a control. Plants treated with the AB Mix were significantly superior to those plants treated with the hard-lipped barb farming wastewater, demonstrated by taller plants, more and larger leaves, larger stem diameter and leaf area, longer roots, greater fresh and dry weight, as well as a higher leaf nitrate content. The aquaculture wastewater at the tested fish density in this study did not support optimal growth of lettuce, so lettuce production is still very low compared to those grown with the AB mix.